2021
DOI: 10.1103/physrevb.103.045203
|View full text |Cite
|
Sign up to set email alerts
|

Giant Nernst effect and field-enhanced transversal zNT in ZrTe5

Abstract: Thermoelectric materials can recover electrical energy from waste heat and vice versa, which are of great significance in green energy harvesting and solid state refrigerator. The thermoelectric figure of merit (zT) quantifies the energy conversion efficiency, and a large Seebeck or Nernst effect is crucial for the development of thermoelectric devices. Here we present a significantly large Nernst thermopower in topological semimetal ZrTe5, which is attributed to both strong Berry curvature and bipolar transpo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Fig. 4a compares the mobility and Nernst thermopower of a few topological materials, including WTe 2 , ZrTe 5 36 , NbP 8 , and Cd 3 As 2 37 , as well as Bi single crystals 29,30 . The Nernst signal strength has a positive correlation with the charge-carrier mobility.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fig. 4a compares the mobility and Nernst thermopower of a few topological materials, including WTe 2 , ZrTe 5 36 , NbP 8 , and Cd 3 As 2 37 , as well as Bi single crystals 29,30 . The Nernst signal strength has a positive correlation with the charge-carrier mobility.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 4c summarizes the Nernst PF values of WTe 2 and other topological semimetals, including NbP 8,40 , ZrTe 5 36 and Cd 3 As 2 37 , with a comparison of the Seebeck PF values of most of the wellknown longitudinal thermoelectric semiconductors [41][42][43][44][45][46][47][48][49] . The topological semimetals, particularly WTe 2 , have high PF values, which are even 2-3 orders of magnitude higher than those of the best thermoelectric semiconductors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When a magnetic field in applied, the magnetic field can split a Dirac node into a pair of Weyl nodes with opposite chirality, and then a nonzero Berry curvature is generated. It has been found that the Berry curvature can induce an anomalous Nernst effect to add on the conventional one 6 , 49 51 . At low magnetic field and low temperature, it is predicted theoretically that the total Nernst effect is characterized by an almost steplike profile at the low magnetic field and the response is dominated by the anomalous Nernst effect 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%